Evolution of paddle federal licenses in Andalucía (2009-2016) - Fernández-Martínez, N.; Gómez-Chacón, R.; Bernal-García, A.; Pérez-Villalba, M. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2018)
The last years of sport in Spain show a high growth in the practice of paddle (Gómez-Chacón, Pascua-Barón and Fernández-Martínez, 2017). The paddle, is the sport of racket more practiced weekly by the Spanish population (Superior Council of Sports, 2015). Likewise, and following the line of other authors, paddle is the sport that has most developed in the last 23 years with a growth of 1,947.41% (López, 2017). The objective of this study is to know the evolution of the federative paddle licenses in Andalusia in absolute category during the years 2009-2016 in order to certify that all the data found coincide with what various authors and public bodies have affirmed. The database of the Andalusian federation of Paddle was consulted. All the data extracted in the consulted bibliography do not do more than indicate that the paddle is one of the most emergent sports and with greater growth of the XXI century.